Aprendizagem histórica intercultural a partir dos contextos educacionais indígenas e não indígenas - Silva, Luciana Leite da (2019)
This thesis seek to contribute to debates on ethnic-racial relations in school education. We recognize progress regarding the new educational guidelines on this theme as they establish that teaching the history of Africa and indigenous peoples is mandatory. However, we understand that the recent reformulations produced in schoolbooks, as well as the overfocus on the idea of respect for differences, are insufficient because the permanence of theoretical and conceptual orientations arising from a Eurocentric conception of world history continues. We defend the idea that we need to go beyond the recognition of the existence of different cultures. We must dedicate ourselves to build an intercultural historical learning that brings complexity and epistemic variety and escapes from the chosen patterns of developed society, progress and civilization. Impacts of this pattern are easily seen when a central role is attributed to the Greek Classical Civilization, regarded as the founder of all Western thought tradition. Hence, we carry out a critical analysis, based on the methodological theoretical framework modernity/coloniality/decoloniality, and categories that were formulated in this context and were also in feedback along the construction of Modern Europe. We consider that, sided with Greek philosophical rationalism, Christianity is a fundamental cultural matrix to think about power over the body, nature, ways of thinking, social organization and spirituality. As the Catholic Church was an active participant in the colonization process, we practiced a decolonial critique of the principles of this religion that imposes itself as universal. Since the concept of coloniality encompasses a continuity of societal, political, ecological and epistemic practices beyond the colonial period, we researched how these aspects had impact on the construction of the Brazilian historiographical matrix. In field research, we analyze student-produced narratives to assess how far we moved beyond the historiographic former understanding of our colonial past and the history of indigenous populations. Finally, we argue that all this criticism of the epistemic basis of Western thought in Brazilian historiography and school education comes from and is closely linked to the criticisms of the Indigenous Movement and their discussions on interculturality. Hearing indigenous researchers, teachers and leaders, we open ourselves to the possibility of rewriting some history and to fill the numerous blank pages resulting from the monotopic path that still underlies the historical narrative inside school education.